Pengaturan Pengunjung dan Kenyamanan Wisatawan di Atraksi Wisata Taman Margasatwa Ragunan - Nungky Puspita; Made Adhi Gunadi; Rizka Novi Irianti (Fakultas Pariwisata Universitas Pancasila, 2014)
In recent years, Ragunan Zoo is always crowded with visitors, especially during the holidays. This study aims to determine the visitor arrangement in Ragunan Zoo and its influence to visitor comfortness using variables derived from Parks and Benefits (2013). Research conducted through distributing questionnaires to Ragunan Zoo visitor and interviews to the parties concerned. The result showing that visitor arrangement of Ragunan Zoo is applied only in aspects of visitor zone arrangement, providing tour guide, and developing approriate marketing strategies.